Dinâmica e transmissão cultural do conhecimento etnobotânico em uma comunidade rural da região semiárida da Paraíba - Marín, Edna Arévalo (2014)
The value of vegetal resources becomes dependent on demographic factors emphasizing the need for researching these issues in rural communities. The present study documents knowledge dynamics and patterns depending on age and gender in use of native plants in a rural community at semiarid region of Paraíba, Northeast Brazil. Socioeconomic factors and ethnobotanical data were registered from 123 household heads through semi-structured interviews. Principal Component Analysis (PCA) was used to evaluate similar uses between species. Comparisons between men and women knowledge and between age groups about species richness, number of citations mentioned as well as species-plants use knowledge measures were made to determine inter-and intra-cultural variations. The findings will reveal what age and gender were important elements of knowledge. In general, elder individuals showed greater knowledge than those younger, in addition, differential knowledge between men and women in some categories confirms occurrence of intra-cultural variations associated with gender. These outcomes show that differentiation of botanical knowledge from a gender and age perspective reinforces the importance of recognizing specific activities and needs in men and women on the design and definition of sustainable management strategies, policies and economic interventions over vegetation legacy, also acting as a priority inclusion indicator of certain species in conservation processes as a contribution to the culture and biodiversity conservation.